Therapeutic neck dissection in head and neck melanoma patients: Comparing extent of surgery and clinical outcome in two cohorts. Issue 9 (September 2021) - Berger, Danique M.S.; Verver, Danielle; van der Noort, Vincent; Grünhagen, Dirk J.; Verhoef, Cees; Al-Mamgani, Abrahim; Zuur, Charlotte L.; van Akkooi, Alexander C.J.; Balm, Alfons J.M.; Klop, W. Martin C.
Abstract: Background: The extent of surgical management of regional lymph nodes in the treatment of cutaneous head and neck melanoma on and anterior to O'Brien's watershed line is controversial. By comparing patients' cohorts of two separate melanoma expert centers we investigate the effectiveness of comprehensive versus (super-) selective neck dissection approach. Methods: Sixty patients with macroscopic (palpable) neck node metastases (N2b) from anterior scalp and face melanoma were retrospectively studied. Forty therapeutic modified radical neck dissections (MRND; levels I–V) combined with elective parotidectomy from The Netherlands Cancer Institute (NCI) were compared with 16 (super-) selective neck dissections [(S)SND; 3–4 levels] and 4 solely MRNDs from Erasmus Medical Center (EMC). Cohorts were analyzed for site of recurrence, overall survival (OS), melanoma-specific survival (MSS), and disease-free survival (DFS). Results: Clinical characteristics of patients were equal in both groups. In the NCI cohort 62.5% (n = 25) of patients recurred versus 65% (n = 13) in the EMC cohort. None of the NCI recurrences affected the parotid gland in contrast to 3 patients in the EMC group. Survival characteristics were not different between the two groups: OS (p = 0.56), MSS (p = 0.98), DFS (p = 0.92). Conclusion: This study does not support to continue the practice of routine elective parotidectomy and MRND in melanoma patients undergoing a lymph node dissection for macroscopic (palpable) nodal disease and justifies (S)SND.